Tipologi Fatwa Kontemporer Dalam Hukum Islam - Nurkhalis Muchtar (Bahasa Indonesia, 2026)
Fatwa is the process of providing answers to problems that arise or questions that emerge. The need of the Muslim community for fatwas has been felt since the early development of Islam. In Islam, fatwa holds a high position, so not everyone is allowed to issue a fatwa. A fatwa originating from someone who is not an expert will cause fatal errors in society. Islamic scholars have written their thoughts on the procedures of issuing fatwas in many works. However, as far as the reading goes, no work has been found that examines the typology of contemporary scholars' fatwas, especially through their written works in Islamic law. On the other hand, there is also the emergence of inappropriate paradigms in issuing fatwas; some are very rigid and textual, while on the other hand, some are too detached from the discourse of fatwa studies. This research uses a descriptive qualitative method on library data findings, with a library research and content analysis approach. It can be concluded that contemporary scholars have different typologies in issuing fatwas. This research also reveals that there are many contemporary and classical fatwa books that have different styles and typologies of fatwas. By understanding the typology of fatwas, it is expected to be a way to understand the existing differences in fatwas, so that stability and peace in diversity and mutual respect can be created, thereby realizing a conducive climate and atmosphere.